2016
DOI: 10.1152/jn.01074.2015
|View full text |Cite
|
Sign up to set email alerts
|

Shape-independent object category responses revealed by MEG and fMRI decoding

Abstract: Kaiser D, Azzalini DC, Peelen MV. Shape-independent object category responses revealed by MEG and fMRI decoding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
64
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 23 publications
7
64
2
Order By: Relevance
“…It should be noted that previous studies provided some evidence for a contribution of semantic object properties to the MEG signal even at relatively early latencies (<250 ms) (Clarke et al, 2015;Coggan et al, 2016;Kaiser et al, 2016b). These studies differed from the current study in several important ways.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…It should be noted that previous studies provided some evidence for a contribution of semantic object properties to the MEG signal even at relatively early latencies (<250 ms) (Clarke et al, 2015;Coggan et al, 2016;Kaiser et al, 2016b). These studies differed from the current study in several important ways.…”
Section: Discussioncontrasting
confidence: 90%
“…It is likely that the semantic factors in these studies (e.g., the property "has legs"; Clarke et al, 2015) would still express in perceptual similarity differences in tasks like the oddball visual search task used here. Second, two of these studies included human faces (Coggan et al, 2016) or bodies (Kaiser et al, 2016b). The human visual system is particularly sensitive to such stimuli (Stein et al, 2012), showing highly selective and localized face-and bodyselective responses in fMRI (Kanwisher, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…By orthogonalizing category membership and visual features of visual stimuli, previous studies reported a residual categorical effect in VOTC, highlighting how some of the variance in the neural data of VOTC might be explained by high-level categorical properties of the stimuli even when the contribution of the basic lowlevel features has been controlled for (Bracci & Beeck, 2016;Kaiser, Azzalini, & Peelen, 2016;Proklova, Kaiser, & Peelen, 2016). Category-selectivity has also been observed in VOTC during semantic tasks when word stimuli were used, suggesting an involvement of the occipito-temporal cortex in the retrieval of category-specific conceptual information.…”
Section: Discussionmentioning
confidence: 97%
“…To test 170generalisation between the conditions, we trained classifiers on all time points in the data from the 5Hz 171 sequences and tested them on all time points in the data from the 20Hz sequences. We repeated this 172 for the inverse (training on 20Hz and testing on 5Hz), and averaged the resulting time-generalisation 173 matrices(Kaiser, Azzalini, & Peelen, 2016). 174 175 All steps in the decoding analysis were implemented in CoSMoMVPA(Oosterhof et al, 2016).…”
mentioning
confidence: 99%